Запорошена плазма в режимі розпаду та формування вуглецевих нанотрубок в плазмі - Бурмака, Г.П.; Burmaka, G.P. (Харків: ХНУ імені В. Н. Каразіна, 2017)
Burmaka G.P. Dusty plasma in afterglow regime and formation of carbon nanotubes in plasma. – Manuscript. Thesis for the scientific degree of candidate of sciences in Physics and Mathematics by speciality 01.04.08 – Plasma Physics. – V.N. Karazin Kharkiv National University, Kharkiv, 2017. The thesis is devoted to the theoretical study of the effect of metastable atoms and electron secondary emission at ion-electrode collisions on a dusty plasma afterglow, and the theoretical study of the growth of vertically-aligned single-walled carbon nanotubes in plasma. The properties of dusty plasma in the afterglow regime and the growth rates of forest of single-walled carbon nanotubes in plasma are studied. A model of constant density for an argon dusty plasma afterglow is developed. In particular, physical processes taking place in argon/dusty plasma afterglow, when charge density of dust particles is larger than the density of electrons, are investigated. The influence of electron generation in metastable-metastable collisions on electron density is studied. It is shown that the electron generation in metastable-metastable collisions may significantly affect the electron density in a dusty plasma afterglow due to higher metastable densities in dusty plasmas comparing with those in the dust-free case. This process provides an increase of electron density at the beginning of the dusty plasma afterglow. It is found that the electron temperature decreases faster in the dusty plasma afterglow comparing with that in the dust-free case because of the electron energy loss on dust particles.
Dusty plasma in afterglow regime and formation of carbon nanotubes in plasma
У дисертаційній роботі вивчені властивості запорошеної плазми в режимі розпаду і формування лісу одношарових вуглецевих нанотрубок в плазмі. Зокрема, проведено дослідження фізичних процесів, що відбуваються в запорошеній аргоновій плазмі в режимі розпаду в умовах, коли концентрація заряду пилових частинок більше концентрації електронів. Показано, що генерація електронів в зіткненнях метастабільних атомів один з одним може істотно вплинути на густину електронів в запорошеній плазмі в режимі розпаду. Вивчено вплив вторинної електронної емісії при зіткненнях іонів з електродами на властивості сильно запорошеної аргонової плазми в режимі розпаду. Показано, що вторинна емісія може збільшити концентрацію електронів в запорошеній плазмі, що є в режимі розпаду, приблизно на десять відсотків. Досліджено формування лісу одношарових вуглецевих нанотрубок при плазмохімічному осадженні з газової фази з урахуванням неоднорідності осадження нейтральних частинок та іонів з плазми на поверхню нанотрубок. Показано, що в присутності плазми ліс нанотрубок може мати більшу довжину, ніж в разі їх зростання без плазми. Визначено, за яких умов формується вуглецева плівка між нанотрубками, яка заважає формуванню нанотрубок. Показано, що залежності швидкостей росту лісу одношарових вуглецевих нанотрубок від довжини нанотрубок істотно відрізняються при низьких і високих температурах.
Keywords: Research Subject Categories::SOCIAL SCIENCES::Social sciences::Education; Research Subject Categories::NATURAL SCIENCES; запорошена плазма; вторинна емісія; вуглецеві нанотрубки; плазмохімічне осадження; dusty plasma; secondary emission; carbon nanotubes; plasma-enhanced chemical vapor deposition